The Outbreak of Honey-bee Mite in Irian Jaya - Kasno . (Media Konservasi, 1989)
Recently the outbreak of parasitic bee mite has occured in several apiaries of Irian Jaya Province.The parasitic bee mite was reported to be Varroa jacobsoni Oud. It was reported that the outbreak has caused beekeepers lost their bees due to the absconding of some bee colonies, so that no honey was produced. Irian Jaya was previously claimed to be free of V. jacobsoni. If the identification of reported bee mite is correct, the way of bee mite introduction into Irian Jaya is inquired. To answer the question, some possibilities of mite introduction are discussed. Some control techniques are mentioned.